Kepemimpinan Visioner : Strategi Transformasi Pendidikan di Era Digital - Mudawiyah, Hidayatul (Maliki Interdisciplinary Journal, 2025)
The advancement of the digital era has significantly transformed the education sector, necessitating visionary leadership as a strategic solution . This type of leadership plays a crucial role in formulating long-term visions, inspiring positive change, and leveraging technological innovation to empower educational communities. This article explores strategic steps that educational leaders can adopt, such as technology integration, enhancing digital skills, and fostering a responsive learning culture.Furthermore, the article emphasizes the importance of leaders in building an educational environment that promotes collaboration, creativity, and continuous learning. Through a visionary approach, education can adapt to contemporary demands while preparing a competent generation to face the future. Practical recommendations are provided as a guide for educational leaders to maximize the potential of the digital era in driving educational transformation.